A comparison between austroads pavement structural design and AASHTO design in flexible pavement - Ghadimi, Behzad; Nikraz, Hamid; Leek, Colin; Nega, Ainalem (Trans Tech Publications Inc, 2013)
This study deals with the Austroads (2008) Guide to Pavement Technology Part 2: Pavement Structural Design on which most road pavement designs in Australia are based. Flexible pavement designs and performance predictions for pavements containing one of more bound layers derived from the mechanistic Austroads pavement design methodology and the AASHTO-2004 approach are compared for Australian conditions, with consideration of subgrade and other material properties and local design preferences. The comparison has been made through two well-known programs namely CIRCLY (5.0) and KENLAYER. The study shows that each guide has its own advantages and disadvantages in predicting stress and strain in pavement layers under different conditions. The study recommends that modifications are necessary resulting in more realistic and longer lasting pavements in Australia.